2019
DOI: 10.1002/kjm2.12088
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐gated sodium channel 1.7 expression decreases in dorsal root ganglia in a spinal nerve ligation neuropathic pain model

Abstract: The role of the voltage-gated sodium channel 1.7 (Nav1.7) is unclear in models of neuropathic pain induced by nerve injury. In the present study, we measured expression levels of Nav1.7 in two distinct neuropathic pain models: spinal nerve ligation (SNL) and chronic constriction injury (CCI). In the SNL model, both mRNA and protein levels of Nav1.7 were markedly lower in the L5 dorsal root ganglia (DRG) but were significantly higher in the L4 DRG. Nav1.7 protein levels were notably higher in both L4 and L5 DRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Also Nav1.7 is illustrated to play important roles in the development of neuropathic pain. Nav1.7 protein levels were notably increased in L4-L5 DRGs under CCI conditions and is suggested to be one promising effector protein correlated with pathogenesis of neuropathic pain [13]. Considering that miR-182 is the downstream effector of Sirt1 and miR-182 downregulates Nav1.7 expression to relive neuropathic pain in a previous study [14], we hypothesized that Sirt1 might downregulated Nav1.7 expression via miR-182.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Also Nav1.7 is illustrated to play important roles in the development of neuropathic pain. Nav1.7 protein levels were notably increased in L4-L5 DRGs under CCI conditions and is suggested to be one promising effector protein correlated with pathogenesis of neuropathic pain [13]. Considering that miR-182 is the downstream effector of Sirt1 and miR-182 downregulates Nav1.7 expression to relive neuropathic pain in a previous study [14], we hypothesized that Sirt1 might downregulated Nav1.7 expression via miR-182.…”
Section: Discussionmentioning
confidence: 92%
“…The downstream effector and pathway after resveratrol-initiated Sirt1 activation hasn't been well elucidated. Considering miR-182 is the downstream effector of Sirt1 and miR-182 is reported to decrease Nav1.7 expression, one promising effector protein of neuropathic pain [13], to relive symptoms related with neuropathic pain [14], we hypothesized that Sirt1 might downregulated Nav1.7 expression via miR-182.…”
Section: Introductionmentioning
confidence: 99%
“…This VGSC is predominantly localized in the peripheral nervous system, and many studies have reported a strong correlation between Na V 1.7 function and many pain states in rodents and humans [ 20 ]. However, the role of Na V 1.7 in neuropathic pain remains uncertain, as contradictory results have been reported in rodents and humans, with some studies showing upregulation [ 27 , 34 , 40 , 41 , 45 ], and others downregulation [ 24 , 28 , 39 ] in primary sensory neurons. In addition, mice lacking Na V 1.7 normally developed neuropathic pain after peripheral nerve injury [ 48 ].…”
Section: Role Of Ttx-sensitive Voltage-gated Sodium Channels (Vgscs) In Neuropathic and Cancer Painmentioning
confidence: 99%
“…Both Nav1.7 and Nav1.8 channels can contribute to nociceptor activity and have been implicated in pain syndromes in humans (McDermott et al, 2019). After SNL, uninjured neurons show an increase in mRNA and protein levels of Nav1.7 and Nav1.8 thought to contribute increases in spontaneous activity (Zhang et al, 2004;Li et al, 2019). While other studies have reported no change in Nav1.7 at the level of mRNA after SNL (Fukuoka et al, 2012), a decrease in Nav1.7 protein and mRNA expression has been reported in injured neurons (Li et al, 2019).…”
Section: Excitability and Spontaneous Activity In C-fibersmentioning
confidence: 99%
“…After SNL, uninjured neurons show an increase in mRNA and protein levels of Nav1.7 and Nav1.8 thought to contribute increases in spontaneous activity (Zhang et al, 2004;Li et al, 2019). While other studies have reported no change in Nav1.7 at the level of mRNA after SNL (Fukuoka et al, 2012), a decrease in Nav1.7 protein and mRNA expression has been reported in injured neurons (Li et al, 2019). After L6 SNL in monkey, injured and uninjured C-fibers showed increased spontaneous activity along with increased α-adrenergic sensitivity in uninjured nerve fibers (Ali et al, 1999).…”
Section: Excitability and Spontaneous Activity In C-fibersmentioning
confidence: 99%